Interface-modulated uniform outer nanolayer: A category of electrodes of nanolayer-encapsulated core-shell configuration for supercapacitors. (March 2021) - Kavinkumar, T.; Seenivasan, Selvaraj; Lee, Hong H.; Jung, Hyeonjung; Han, Jeong Woo; Kim, Do-Heyoung
Abstract: Capacity and cyclic stability are two major issues of interest for supercapacitors. We report here a category of electrodes that are core-shell type that is encapsulated by a uniform outer nanolayer. We demonstrate the efficacy of the type of electrodes with a model electrode of NiCo2 O4 /MoO2 core-shell encapsulated by atomic layer-deposited NiO nanolayer. The electronic modulation at the interface created by the outer nanolayer, verified by instrumental analysis and DFT calculations, provides a substantial amount of additional capacity, which is more than 450 C g −1 for the model electrode. The thin outer nanolayer becomes much suppler by drastic decrease in flexural rigidity, which is proportional to the third power of the thickness. This flexibility afforded by the thin nanolayer helps preserve the physical integrity of the encapsulated inner structure, thereby reducing the loss in capacity to less than 3% from more than 10% after 20, 000 cycles of charge and discharge for the model electrode. An asymmetric supercapacitor with the model electrode and a carbon-based anode delivers an energy density of 136 W h kg −1 at a power density of 1800 W kg −1 . This result is an indication that the nanolayer-encapsulated core-shell type electrodes would in due time put supercapacitors squarely on the map of lithium ion battery in terms of energy density but at the power density typical of capacitors. Graphical Abstract: ga1 Highlights: A category of electrodes is introduced on the basis of a classical mechanics theory and interface engineering to address the issues of energy storage capacity and lifetime of supercapacitor (cyclic stability). A model electrode of the category increases the capacity by more than 450 C g −1 . Typical capacity ranges from 495 to 1170 C g −1 . The model electrode reduces the loss in capacity after 20, 000 cycles of charge/discharge to less than 3% from more than 10%. The supercapacitor with the model electrode coupled with a carbon-based anode puts its energy density well within the range of lithium ion battery. The category of electrodes would in due time usher in supercapacitors that can replace lithium ion battery with the power density of typical capacitors.